Antiviral and Virucidal Activities of Nα-Cocoyl-L-Arginine Ethyl Ester. (28th November 2011) - Yamasaki, Hisashi; Tsujimoto, Kazuko; Ikeda, Keiko; Suzuki, Yukiko; Arakawa, Tsutomu; Koyama, A. Hajime
Abstract : Various amino acid-derived compounds, for example, N α -Cocoyl-L-arginine ethyl ester (CAE), alkyloxyhydroxylpropylarginine, arginine cocoate, and cocoyl glycine potassium salt (Amilite), were examined for their virucidal activities against herpes simplex virus type 1 and 2 (HSV-1 and HSV-2), influenza A virus (IAV), and poliovirus type 1 (PV-1) in comparison to benzalkonium chloride (BKC) and sodium dodecylsulfate (SDS) as a cationic and anionic control detergent and also to other commercially available disinfectants. While these amino acid-derived compounds were all effective against HSV-1 and HSV-2, CAE and Amilite were the most effective. These two compounds were, however, not as effective against IAV, another enveloped virus, as against HSV. Cytotoxicity of CAE was weak; at 0.012%, only 5% of the cells were killed under the conditions, in which 100% cells were killed by either SDS or BKC. In addition to these direct virucidal effects, CAE inhibited the virus growth in the HSV-1- or PV-1-infected cells even at 0.01%. These results suggest a potential application of CAE as a therapeutic or preventive medicine against HSV superficial infection at body surface.